Volatile profiling and microbiome analysis of papaya fruit rot caused by Colletotrichum gloeosporioides, Lasiodiplodia theobromae, and Fusarium solani and postharvest control strategies - Tan, Guang Heng (2025)
Papaya (Carica papaya) is a vital crop, particularly in tropical countries like Malaysia, due to its rich nutritional content, economic value, excellent flavour, and applications in drug development and industrial processing. The export of fresh papaya and processed papaya products has become a significant source of income for papaya-growing countries, especially in regions where the demand for tropical fruit is high. However, despite these benefits, papaya's climacteric nature makes it highly susceptible to rapid deterioration, primarily due to severe infections by various pathogens that develop both epiphytically and endophytically during postharvest handling. These irreversible decays lead to substantial changes in overall fruit quality and contribute to significant postharvest losses in papaya-producing countries, including Malaysia. To mitigate these losses, understanding the causal agents of these infections is crucial. Early diagnosis and identification methods have been introduced and implemented to detect the spread of diseases, enabling timely interventions. Additionally, various control strategies are applied to inhibit and delay disease establishment through different modes of action. This thesis aims to elucidate the volatile profile of ‘Sekaki’ papaya during ripening and its changes when infected with Lasiodiplodia theobromae, Fusarium solani, and Colletotrichum gloeosporioides. Furthermore, the microbiome of the whole papaya fruit is analysed using next-generation sequencing (NGS) to understand the impact of fruit ripening and rotting on microbial shifts within the fruit. In addition, the potential of an underutilized crop, Garcinia atroviridis, is explored for its ability to inhibit the growth of L. theobromae, F. solani, and C. gloeosporioides at different concentrations. An in-vivo analysis of G. atroviridis fruit extract against C. gloeosporioides is also conducted, along with an assessment of its impact on the physico-chemical qualities of papaya when applied at varying concentrations.